Finite-time ruin probability of a perturbed risk model with dependent main and delayed claims - Yang, Yang; Wang, Xinzhi; Zhang, Zhimin (Nonlinear Analysis: Modelling and Control, 2021)
This paper considers a delayed claim risk model with stochastic return and Brownian perturbation in which each main claim may be accompanied with a delayed claim occurring after a stochastic period of time, and the price process of the investment portfolio is described as a geometric Lévy process. By means of the asymptotic results for randomly weighted sum of dependent subexponential random variables we obtain some asymptotics for finite-time ruin probability. A simulation study is also performed to check the accuracy of the obtained theoretical result via the crude Monte Carlo method.
Keywords: finite-time ruin probability; main and delayed claims; stochastic return; subexponential distribution; dependence